Impact of Blade Geometric Parameters on the Specific Cutting Energy of Willow (Salix viminalis) Stems - Tomasz Nowakowski; Karol Tucki (Applied Sciences)
This article presents a model to estimate the specific energy demand for cutting annual willow stems, considering variations in plant moisture content and sliding-cutting angles. The study involved laboratory tests and statistical analyses. Key parameters were measured for 50 randomly selected annual willow shoots, including total plant weight, leaf weight, stem weight, centre of gravity of the shoot, shoot length, and stem diameter at specified heights: 0, 150, 500, 750, 1000, 1250, 1500, and 2000 mm. Five levels of willow shoot moisture content were evaluated. The study established a cutting force-deformation relationship through strength tests with an accuracy of 1 N, which was subsequently used to calculate shear stress and specific cutting energy. Steel blades with an angle of 30° and sliding-cutting angles of 0°, 15°, 30°, and 45° were used in the study. Ten repetitions were performed for each combination of variable parameters: shoot moisture content and blade sliding-cutting angle. Experimental results were evaluated using analysis of variance (ANOVA), while Duncan’s test was applied to identify and classify groups with homogeneous specific energy values. The developed characterisation offers valuable information for designing shredding units and optimising their operational parameters to reduce energy consumption.